Mengukur risiko pembiayaan terhadap pembiayaan murabahah dengan menggunakan moderated regression analysis - Apriliani, Fajar; Rofiuddin, Mohammad (Journal of Accounting and Digital Finance, 2022)
This study analyzes the effect of capital adequacy and financing-to-deposit ratio profit margin on Murabaha financing with financing risk as a moderating variable. This study uses secondary data in the form of panel data. The population in this study were all Islamic Commercial Banks registered with the Financial Services Authority (OJK) for the 2016-2020 period, namely BRI Syariah Banks, BNI Syariah Banks, BCA Syariah Banks, Mandiri Syariah Banks, Muamalat Indonesia Banks, Mega Syariah Banks, Victoria Syariah Banks, Bank Panin Dubai Syariah, Bank Jabar Banten Syariah, Bank Syariah Bukopin. The sample of this study amounted to 10 Islamic Commercial Banks. The data analysis method approach used is Moderated Regression Analysis. The results of this study indicate that Capital Adequacy does not affect Murabahah Financing. FDR harms Murabaha Financing. Profit Margin has a positive effect on Murabaha Financing. NPF does not moderate the effect of CAR on Murabahah Financing. NPF moderates the effect of FDR on Murabahah Financing. NPF moderates the effect of Margin on Murabahah Financing.